Effect of Heat Stress, Dietary Electrolytes, and Vitamins E and C on Growth Performance and Blood Biochemistry of the Broiler Chicken - Livingston, Matthew L.; Pokoo-Aikins, Anthony; Frost, Thomas; Laprade, Lisa; Hoang, Vy; Nogal, Bartek; Phillips, Chelsea; Cowieson, Aaron J. (Frontiers in Animal Science, 2022)
A total of 960 broilers were used to determine the effect of heat stress and dietary electrolyte balance on blood biochemistry. Chicks were sex sorted and allocated to 48 pens with 20 chicks per pen (10 males and 10 female) creating 6 treatments (3 diets x 2 house environments) with 8 replicates. Birds were fed one of three dietary treatments: a control containing primarily sodium chloride (NaCl), a heat stress formulation containing bicarbonate (NaHCO3), or heat stress fortified with 200 ppm vitamin C and E (NaHCO3 Fortified) were housed in two different temperature-controlled environments. ( thermoneutral environment (Control) or heat stressed (Heat Stress). Venous blood from 2 broilers per pen were analyzed at day 28, 35 and 42 using the i-STAT® Handheld Clinical Analyzer, Abaxis Vetscan VS2, iCheck™ FLUORO devices, while malondialdehyde, heterophile, and lymphocyte counts were also determined. Performance was measured at weekly intervals. Mortality was significantly higher in broilers exposed to heat stress as compared to thermoneutral, while broilers that received dietary sodium chloride also had higher mortality than bicarbonate fed birds. Age created a highly significant linear impact on blood calcium, phosphorus, potassium, sodium, chloride, carotene, aspartate aminotransferase, creatine kinase, uric acid, total protein, albumin, globulin, and hematocrit. Heat stress reduced potassium, hematocrit, uric acid, total protein, globulin, hematocrit and lymphocytes, while increasing sodium and glucose compared to broilers in a thermoneutral environment. Broilers fed dietary sodium chloride had increased blood potassium and chloride, and reduced sodium compared to those fed bicarbonate and vitamin fortified diets. Total blood carbon dioxide increased in broilers fed bicarbonate and vitamin fortified diets when compared to birds fed only sodium chloride. This study demonstrates that blood biochemistry of modern broilers is influenced by dietary intervention and changing environmental conditions. This pattern suggests a blood biomarker footprint of sub-optimal nutrition or poor environmental conditions that may provide valuable information into physiological changes in response to dietary electrolytes, vitamins and heat stress. Furthermore, this footprint may potentiate the development of diagnostic tools, combining biomarkers to determine nutrition and health status of individual broiler flocks, for nutritionists, veterinarians and live production managers.